Frailty In Older Adults Attending An Outpatient Geriatric Clinic As Measured By The Visual Scale Of Frailty - Marco Túlio Gualberto Cintra; Felipe Ferreira Guimarães; Cislene Teixeira de Souza; Fernanda Silva Trindade Luz; Érica Dias Murta; Maria Aparecida Camargos Bicalho; Edgar Nunes de Moraes (Brazilian Society of Geriatrics and Gerontology, 2024)
BACKGROUND: Existing instruments for the diagnosis of frailty are limited by their focus on mobility evaluation, failure to incorporate comorbidities, and dichotomous classification of patients as frail or non-frail, which hinders adequate identification of frail older adults. OBJECTIVE: To evaluate the frailty profile of outpatients seen at a secondary geriatric care service in Belo Horizonte, Brazil, as measured by the Visual Scale of Frailty, and describe the five levels of health status proposed by this instrument in terms of function, disabilities, and comorbidities. METHODS: The medical records of patients who attended the clinic between February 2011 and February 2014 were evaluated, and the patients classified in accordance with the Visual Scale of Frailty. Continuous variables were analyzed by ANOVA or the Kruskal-Wallis test, and categorical variables, by the χ2 test. Analyses were performed in SPSS Version 19.0. RESULTS: A total of 813 medical records were evaluated. Among these patients, 5.2% were considered robust, 31% at risk of frailty, 24.6% as frail, 34.8% as highly complex frail, and 4.4% as frail individuals in the final stage of life. Analysis of the health status categories demonstrated an association between these categories, greater functional impairment, and greater presence of disabilities and comorbidities. CONCLUSION: The Visual Scale of Frailty is a useful tool in assessing the health status of older adults and indicated a high prevalence of frailty in the studied population.